Strategi Dakwah Tuangku Ridwan dalam Pembinaan Masyarakat di Jorong Kampung Apar Kecamatan Batang Anai Kabupaten Padang Pariaman - Nur’aini; Tomi Hendra (Lembaga Yasin AlSys, 2026)
Da’wah strategies constitute an important element of community development, particularly in enhancing the understanding and practice of religious values. However, studies on the application of da’wah strategies by religious leaders within local communities, particularly by Tuangku Ridwan in Jorong Kampung Apar, remain limited. This study aims to analyze the da’wah strategies and materials employed by Tuangku Ridwan in developing the community of Jorong Kampung Apar, Batang Anai Subdistrict, Padang Pariaman Regency. The study employed a qualitative approach with a descriptive design. Data were collected through observations, interviews, and documentation involving Tuangku Ridwan and community members who participated in da’wah activities and were subsequently analyzed descriptively to identify the types of da’wah strategies and materials employed. The findings indicate that Tuangku Ridwan employed three types of da’wah strategies: sentimental, rational, and sensory strategies. The sentimental strategy was implemented through a gentle approach, the provision of advice, and attentiveness to the community’s circumstances. The rational strategy was implemented through question-and-answer sessions and discussions, whereas the sensory strategy was implemented through religious activities and exemplary conduct. The da’wah materials encompassed aspects of Islamic creed, Islamic law, and morality. This study concludes that the community development undertaken by Tuangku Ridwan integrates emotional, intellectual, and practical approaches so that religious messages can be received in accordance with the circumstances of the local community. These findings contribute to the development of local community-based da’wah studies and provide practical implications for preachers in designing strategies that are contextual, communicative, and oriented toward exemplary conduct. Future research should broaden the geographical scope and informant characteristics and analyze community acceptance of each da’wah strategy.